Correlation between the intercanine dimension and the mesiodistal diameter of the permanent first molars - Chan, Iris; Macapanpan, Luz C. (Adviser).
The purpose of this paper was to explore the possibility of the existence of a correlation between the intercanine dimension and the first permanent molars' mesiodistal diameters. Measurements were obtained from casts of two groups: one with well-aligned anterior teeth and the other with mal-alignment of the anterior teeth. Results indicate the possibility of a correlation between mesiodistal diameter and the intercanine dimension in well-aligned cases but not in mal-aligned cases. However, a more definite research and larger sample with more attention to sex differences and interrelation between the maxillary and mandibular factors.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Molars